Partitioning of potentially toxic elements among two colloidal fractions and relevance for their mobility in different water types - Moreno Filipa; Valente Teresa; Gomes Patrícia; Fonseca Rita; Costa Maria Rosário; Costa Ana (E3S Web of Conferences, 2019)
Potentially toxic elements are mobilized in aquatic systems in solution or bounded to colloids of different sizes, which may include nanometer particles. The present work studies the distribution of elements (Al, Fe, Zn, Mn, Co, Cd, Ni, Cu, and As) between small (<0.20 μm) and larger (0.45–0.20 μm) colloids in different waters sources in a world class metallogenic province (Iberian Pyrite Belt), including the acid mine waters. Syringe filters with pore-size ratings of 0.20 μm and 0.45 μm have been used to assess the transport and fate of these potentially toxic elements. The results show the contribution of colloids for mobility of arsenic and most metals, evidencing the role of the small ones in acid mine drainage.